Ab initio calculations of ideal and defective bismuth telluride nanotubes. Issue 3 (27th October 2014) - Pokropivny, Alex; Xiong, Shiyun; Chumakov, Yurii; Cortona, Pietro; Volz, Sebastian
<x xml:space="preserve">Abstract</x> Stability and electronic structures are analyzed for ideal bilayer and trilayer Bi–Te nanotubes and for trilayer nanotubes with exchanged‐pair, antisite, and vacancy defects with a first‐principle method. Cohesion energy calculations reveal the high stability of those nanotubes, the most stable being the trilayer nanotube with semicube patterns. Crystal of nanotubes is more stable than individual nanotubes. From the electronic structure analysis, nanotubes with single Te antisite, Bi antisite, and Te vacancy defects are found to be metallic. Instead, the Bi vacancy defected nanotube is characterized by a semiconductor behavior with promising thermoelectric properties for nanoscale devices.